Evaluating circulating tumour cell enrichment techniques to establish an appropriate method for clinical application in glioblastomas - Barber, Hannah R.; Perks, Claire M.; Kurian, Kathreena M. (Frontiers in neurology, 2024)
Brain tumours reduce life expectancy for an average of 20 years per patient, the highest of any cancer. A third of brain tumour patients visit their GP at least five times before diagnosis and many of those are diagnosed late through emergency departments. A possible solution to this challenge is to utilise a “liquid biopsy” blood test designed for circulating tumour cells (CTCs). Such a test could be applied at a primary healthcare centre, contributing to informed decision making for diagnostic imaging referrals. Furthermore, it could also be applied at secondary health care centres for the ongoing monitoring of disease recurrence. There is increased interest in CTC enrichment methods as a potential approach for faster diagnosis and monitoring of disease progression. The aim of this review to compare four CTC enrichment methods - OncoQuick ® , Screen Cell ® , pluriBead ® and Cell Search ® – with the objective of identifying a suitable method for application in the clinical setting for the isolation of CTCs from glioblastomas.